221k views
4 votes
Let a=x^2 + 4. rewrite the following equation in terms of "a" and set it equal to zero. (x^2+4)^2+32=12x^2+48?

User Trystan
by
7.5k points

1 Answer

7 votes
Hello!

So we have (x^2+4)^2+32=12x^2+48 and initial condition of a=x^2+4 and want it rewritten in terms of a and set equal to zero. So we have;

a^2+32=12(x^2+4) so now we have;

a^2+32=12a so now we just get everything on one side to set equal to zero;

a^2 -12a +32=0 is the final answer.

Hope this helps! Any questions please ask! Thank you so much!
User Trenton Tyler
by
7.8k points